A clinical comparison of Atlas and LVIS Jr stent-assisted aneurysm coiling. (4th August 2018) - Gross, Bradley A; Ares, William J; Ducruet, Andrew F; Jadhav, Ashutosh P; Jovin, Tudor G; Jankowitz, Brian Thomas
Abstract : Background: Case series have described the safety and efficacy of LVIS Jr and Atlas stent-assisted aneurysm coiling, but their comparative clinical performance has not yet been formally studied. Objective: To clinically compare LVIS Jr and Atlas stents, emphasizing comparative rates of technical success and complications. Methods: Our institutional endovascular database was queried for aneurysms treated by stent-assisted coiling with either the LVIS Jr or Atlas stents. Demographic data, aneurysm information, treatment technique, periprocedural and device-related complications, and initial and follow-up angiographic results were evaluated. Results: Thirty-seven patients underwent Atlas stent placement and 27 patients underwent LVIS Jr stent placement for aneurysm coiling. There was no significant difference in aneurysm location, size, coiling technique, and coil packing density between the two cohorts. The rate of initial Raymond 1 occlusion was significantly greater in the Atlas cohort (57% vs 41%, P=0.03). The rate of postoperative ischemic complications, both clinically apparent and as defined on postoperative MRI diffusion-weighted imaging, did not significantly differ between the two groups. Follow-up DSA demonstrated a significantly greater rate of Raymond 1 or 2 occlusion for the Atlas cohort (100% vs 81%, P=0.04), and a significantly lower rate of in-stent stenosis (0% vs 19%, P=0.04). Conclusion: This institutional analysis demonstrates greater obliteration rates and lower in-stent stenosis rates for aneurysms treated via Atlas stent-assisted coiling as compared with those treated via LVIS Jr stent-assisted coiling.